1995
DOI: 10.2527/1995.732598x
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal degradation of switchgrass, big bluestem, and smooth bromegrass leaf proteins

Abstract: (. 116 h-l). Major protein fractions that resisted ruminal degradation in both experiments, detected using SDS-PAGE, were at approximate molecular weights of 56, 26, and 24 kDa. For switchgrass and big bluestem, total protein and individual protein fractions were generally at higher concentrations and present for longer periods of time than for smooth bromegrass. This suggests that a mechanism may exist in C4 species that allows certain protein fractions to remain undegraded for longer periods compared with sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
0
8
0
3
Order By: Relevance
“…The hays used in this experiment were chosen because we expected differences in leaf to stein ratios (Cherney et al, 1990) and protein fractions (Sniffen et al, 1992) between these warm-and cool-season grasses. These compositional changes cause distinct rurninal disappearance rates, which in I iirii affect N metabolism (Redfearn et al, 1995). We expected the gamagrass to have a greater leaf to stein ratio and different leaf characteristics than orchardgrass.…”
Section: Expmentioning
confidence: 99%
“…The hays used in this experiment were chosen because we expected differences in leaf to stein ratios (Cherney et al, 1990) and protein fractions (Sniffen et al, 1992) between these warm-and cool-season grasses. These compositional changes cause distinct rurninal disappearance rates, which in I iirii affect N metabolism (Redfearn et al, 1995). We expected the gamagrass to have a greater leaf to stein ratio and different leaf characteristics than orchardgrass.…”
Section: Expmentioning
confidence: 99%
“…More dietary AA reach the small intestine when protein is protected from ruminal degradation, potentially increasing animal performance ( 6 ) . Ruminal degradability of forage CP is highly variable among forage species (5,13,14) and is affected by stage of maturity (9,13). The RDP and RUP of forages may be deficient if they are harvested during certain stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al (2001) also reported a linear decrease (80 to 60 g kg −1 ) in bermudagrass Fraction C as N fertilization level increased from 0 to 156 kg ha −1 harvest −1 Warm‐season grasses tend to allocate protein compounds to chloroplasts. With a greater portion of chloroplasts located within the bundle sheath cells, the slower degradability of the bundle sheath cell wall may favor the enhancement of CP Fractions B and C without affecting Fraction A (Redfearn et al, 1995).…”
Section: Resultsmentioning
confidence: 99%